2005
DOI: 10.1210/er.2003-0034
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Nuclear Receptors with the Wnt/β-Catenin/Tcf Signaling Axis: Wnt You Like to Know?

Abstract: The cross-regulation of Wnt/beta-catenin/Tcf ligands, kinases, and transcription factors with members of the nuclear receptor (NR) family has emerged as a clinically and developmentally important area of endocrine cell biology. Interactions between these signaling pathways result in a diverse array of cellular effects including altered cellular adhesion, tissue morphogenesis, and oncogenesis. Analyses of NR interactions with canonical Wnt signaling reveal two broad themes: Wnt/beta-catenin modulation of NRs (t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
287
0
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 360 publications
(300 citation statements)
references
References 173 publications
9
287
0
4
Order By: Relevance
“…These facts are in agreement with a widespread point of view that there is a close relation among all these receptors, suggesting a complex and tight regulation dependent on secondary messengers and cofactors. This regulation has already been described in macrophages and Wnt signaling in other cell types (61,62) but, to our knowledge, not until now in DCs. In this sense, there would be a nuclear receptor modulation of the DC response depending on the external signaling or the extracellular medium composition, together with an intrinsic stage of the cells.…”
Section: Discussionsupporting
confidence: 56%
“…These facts are in agreement with a widespread point of view that there is a close relation among all these receptors, suggesting a complex and tight regulation dependent on secondary messengers and cofactors. This regulation has already been described in macrophages and Wnt signaling in other cell types (61,62) but, to our knowledge, not until now in DCs. In this sense, there would be a nuclear receptor modulation of the DC response depending on the external signaling or the extracellular medium composition, together with an intrinsic stage of the cells.…”
Section: Discussionsupporting
confidence: 56%
“…15 It has been reported that RAR interacts with β-catenin and inhibits β-catenin-mediated gene transcription. [16][17][18] But, whether there is an interaction and what is the functional regulation between RXRα and β-catenin are not clear. Using mammalian two-hybridization system in vivo and immunoprecipitation in vitro in this study, we found that RXRα directly interacted with β-catenin, and that RXRα directly inhibited β-catenin transcriptional activity and protein expression in colorectal cancer cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…Canonical Wnt signaling converges with various hormone-signaling pathways through interaction with corresponding nuclear receptors. This crosstalk has been shown to play an important role in the regulation of many vital biological processes, including cell proliferation and carcinogenesis (Moon et al, 2004;Mulholland et al, 2005 and references therein).…”
Section: Introductionmentioning
confidence: 99%